2016
DOI: 10.1039/c6nr07237b
|View full text |Cite
|
Sign up to set email alerts
|

In situ electrical modulation and monitoring of nanoporous gold morphology

Abstract: The ability to fine-tune feature size in nanostructured thin films is critical, as many desirable properties of these materials are dictated by their nanostructure. Accordingly, there is a need for techniques that allow for modifying nanostructure while monitoring the morphological changes in situ. Here, we demonstrate a closed-loop electro-annealing system which enables in situ monitoring of morphology evolution in sub-micron nanoporous gold (np-Au) thin films. Np-Au is produced by a microfabrication-compatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…To understand the effect of pore morphology on electrochemical sensing phenomena at the nanolevel, a group of np-Au samples (unannealed np-Au) was thermally annealed, as routinely performed. 44 The median pore radii of unannealed and annealed np-Au electrodes were 24 and 56 nm, respectively, determined by analysis of SEM images (Figure 1a,b). Interconnected noncolumnar pores and the resulting "funnel-like" constrictions are evident in the crosssection images of the two morphologies (Figure 1c,d).…”
mentioning
confidence: 99%
“…To understand the effect of pore morphology on electrochemical sensing phenomena at the nanolevel, a group of np-Au samples (unannealed np-Au) was thermally annealed, as routinely performed. 44 The median pore radii of unannealed and annealed np-Au electrodes were 24 and 56 nm, respectively, determined by analysis of SEM images (Figure 1a,b). Interconnected noncolumnar pores and the resulting "funnel-like" constrictions are evident in the crosssection images of the two morphologies (Figure 1c,d).…”
mentioning
confidence: 99%
“…In order to achieve a better antifouling performance, the pore size need to be decreased to the nanoscale (see Figure 5b) [69]. Seker's group has employed nanoporous Au electrodes to construct low fouling DNA sensors for electrochemical detection of target DNAs in biofluids with a high sensitivity and low limit of detection (LOD) [70][71][72][73][74]. Alex M. Downs et al have showed that the porous Au microelectrode has the ability of detecting aptamers in the living body.…”
Section: Porous Coatingsmentioning
confidence: 99%
“…Various kinds of nanoporous surface have been fabricated in previous studies [33][34][35][36][37]. The high density and uniformity of Au nanoporous substrates make them suitable as SERS substrates.…”
Section: Fabrication Of the Au Nanoporous Sers Substratementioning
confidence: 99%